Change detection in Southern Turkey using normalized difference vegetation index (NDVI) - Alphan, Hakan; Derse, M. Ali (Journal of Environmental Engineering and Landscape Management, 2013)
This study analyzed landscape changes in the Mediterranean using remotely sensed satellite images. Bitemporal Thematic Mapper (TM) scenes of Erdemli (Southern Turkey) acquired by Landsat satellites were analyzed to detect landscape changes in the study area, which supports a mosaic of landscapes from coastline to altitudes over tree line. Visible and near infrared bands (i.e. bands 3 and 4) of the near-anniversary (August) images from 1984 and 2006 were used to derive Normalized Difference Vegetation Index (NDVI) images. NDVI images for the earlier and later dates were analyzed. ASTER and Quickbird images, topographic maps, forest stand maps were used as ancillary data. Spatial distribution of change is mapped and interpreted. Results showed that forest regeneration took place especially in upper lands, while deforestation occurred at lower altitudes in relatively smaller patches in close proximity to the coast and to the roads.First published online: 14 Dec 2012